Bacteriophage lambda carrying the Escherichia coli chromosomal region of the replication origin. - Miki, T (1978)
A transducing phage lambdaasn was isolated. The late gene region of its genome was found to have been substituted by an Escherichia coli chromosomal segment containing the genes bgIR, bgIC, glmS, uncA, and asn. Restriction endonuclease cleavage mapping and electron microscopic analysis of the lambdaasn DNA revealed that the size of the bacterial segment is approximately 1.75 X 10(7) daltons, corresponding to about 26.4 kilobases. The circular DNA of lambdaasn was digested with restriction endonuclease EcoRI, diluted, and sealed with DNA ligase. When the reaction mixture was used to transform a recipient E. coli strain, a small plasmid of about 1 X 10(7) daltons (named pMCR115) was obtained. Restriction endonuclease cleavage mapping of pMCR115 and other evidence suggested that it contained the replication origin (oriC) of the E. coli chromosome.